Evidence of Intramolecular Structural Stabilization in Light Activated State of Orange Carotenoid Protein - McKinney, J. A.; Sharma, A.; Crossen, K.; Deng, Y.; George, D. K.; Lechno-Yossef, S.; Kerfeld, C.; Markelz, A. G. (Biophysical Journal, 2020)
Orange carotenoid protein (OCP) controls efficiency of the light harvesting antenna, the phycobilisome (PBS), in diverse cyanobacteria and prevents oxidative damage. It is the only known photoactive protein that uses a carotenoid, canthaxanthin, as its chromophore. The structure of OCP consists of two globular domains, connected by an unstructured loop, that forms a hydrophobic pocket for the carotenoid. In low light, canthaxanthin bound OCP is inactive and appears orange. Illumination by strong light results in an active state that interacts with the PBS to induce fluorescence quenching, a red appearance and conformational changes that include a 12Å shift by canthaxanthin into the N-terminal domain. Terahertz (THz) dynamical transition measurements and anisotropic terahertz microscopy are used to measure the intramolecular structural dynamics in the inactive and active states, which can be induced by photoexcitation or chaotropic salts. The measurements indicate that the active state has a decrease in structural flexibility, which may be related to enhanced interactions with the PBS.
Keywords: Biophysics

Stabilization of Terahertz Vibrational Modes in Illuminated Orange Carotenoid Protein Crystals - McKinney, J.; Sharma, A.; Deng, Y.; George, D.; Lechno-Yossef, S.; Kerfeld, C.; Markelz, A. (2020 45th International Conference on Infrared, Millimeter, and Terahertz Waves (IRMMW-THz), 2020)
Orange carotenoid protein (OCP) controls efficiency of the phycobilisome (PBS), the light harvesting antenna in cyanobacteria, to prevent oxidative damage. The OCP switches from resting state to photo protective state with intense blue light illumination. Questions persist as to why OCPR interaction increases with the PBS over that with the OCPO. Here we examine the role of long-range intramolecular vibrations within OCP. Using Stationary Sample Anisotropic Terahertz Microscopy (SSATM) we measure changes in the intramolecular vibrations with photo switching. We report the first observation of switching in the intramolecular vibrations with photoexcitation. Results suggest that there is a stiffening of the molecule in the photo protective state. This increase in structural stability may enhance the interaction with the PBS change in OCP interaction with PBS. In low light, carotenoid bound OCP appears orange (OCP o ) and is inactive. Illumination by strong light converts OCP to the active, red (OCPR) state, which interacts with the PBS. A comparison of anisotropic THz microscopy measurements of dark adapted (OCP o ) and illuminated OCP crystals indicate differences in their vibrational modes that may be important for OCP-PBS interactions.

THz Transmission through Submillimeter Apertures - LaFave, T.; Lee, A.; Kao, T.-Y.; Markelz, A. (IRMMW-THz, 2020)
Terahertz near-field microspectroscopy is emerging as an essential tool for characterization of novel materials and biomolecules. It is important to ensure the near field geometry used does not introduce spectral artifacts. For example, many scanning techniques can be strongly influenced by the interaction between the scattering tip and the sample. Here we examine the spectroscopic effects of a 200 μm diameter aperture for THz near-field measurements. We use HFSS to model free-space transmission through samples with resonant absorbance as a function of sample thickness, lateral sample width, and aperture diameter. We examine the transmitted power and spectral fidelity for coupling of transmitted THz light onto a detector. These studies inform corrective post-measurement analysis algorithms and design of near-field detection systems.

Stationary Sample Anisotropic THz Spectroscopy using Discretely Tunable THz Sources - LaFave, T., Jr.; George, D. K.; Markelz, A. G.; McNee, Ian; Kozlov, Vladimir; Schunemann, Peter (2019 44th International Conference on Infrared, Millimeter, and Terahertz Waves, 2019)
We demonstrate anisotropic THz spectroscopy of sucrose using newly developed compact discretely tunable THz sources for turn-key spectroscopic systems.

Tunable Compact Narrow Band THz Sources for Frequency Domain THz Anisotropic Spectroscopy - George, D. K.; LaFave, T. J.; Markelz, A. G.; McNee, I.; Tekavec, P.; Kozlov, V.; Schunemann, P. (Conference on Next-Generation Spectroscopic Technologies XII, 2019)
We demonstrate frequency domain THz anisotropy signature detection for protein crystal models using newly developed compact tunable narrow band THz sources based on Orientation Patterned Gallium Phosphide for turn-key spectroscopic systems.
Keywords: anisotropy; biomolecules; femtosecond; optical rectification; orientation patterned gallium phosphide; Terahertz; THz generation

Increase in Dynamical Collectivity and Directionality of Orange Carotenoid Protein in the Photo-Protective State - Deng, Y. T.; Luck, C. H.; Romo, T. D.; Grossfield, A. M.; Bandara, S.; Ren, Z.; Yang, X. J.; Markelz, A. G. (Biophysical Journal, 2018)
Keywords: Biophysics

Investigation of the Isotope Shift in Protein Collective Vibrations - Luck, C.; Xu, M.; Markelz, A. (APS 2018, 2018)

Measuring Protein Intramolecular Dynamics with Terahertz Light: Functional Changes and Relevance to Biology - Xu, M.; Deng, Y.; Luck, C.; Sharma, A.; Markelz, A. (APS 2018, 2018)

The 2017 terahertz science and technology roadmap - Dhillon, S. S.; Vitiello, M. S.; Linfield, E. H.; Davies, A. G.; Hoffmann, M. C.; Booske, J.; Paoloni, C.; Gensch, M.; Weightman, P.; Williams, G. P.; Castro-Camus, E.; Cumming, D. R. S.; et al. (Journal of Physics D-Applied Physics, 2017)
Science and technologies based on terahertz frequency electromagnetic radiation (100 GHz-30 THz) have developed rapidly over the last 30 years. For most of the 20th Century, terahertz radiation, then referred to as sub-millimeter wave or far-infrared radiation, was mainly utilized by astronomers and some spectroscopists. Following the development of laser based terahertz time-domain spectroscopy in the 1980s and 1990s the field of THz science and technology expanded rapidly, to the extent that it now touches many areas from fundamental science to 'real world' applications. For example THz radiation is being used to optimize materials for new solar cells, and may also be a key technology for the next generation of airport security scanners. While the field was emerging it was possible to keep track of all new developments, however now the field has grown so much that it is increasingly difficult to follow the diverse range of new discoveries and applications that are appearing. At this point in time, when the field of THz science and technology is moving from an emerging to a more established and interdisciplinary field, it is apt to present a roadmap to help identify the breadth and future directions of the field. The aim of this roadmap is to present a snapshot of the present state of THz science and technology in 2017, and provide an opinion on the challenges and opportunities that the future holds. To be able to achieve this aim, we have invited a group of international experts to write 18 sections that cover most of the key areas of THz science and technology. We hope that The 2017 Roadmap on THz science and technology will prove to be a useful resource by providing a wide ranging introduction to the capabilities of THz radiation for those outside or just entering the field as well as providing perspective and breadth for those who are well established. We also feel that this review should serve as a useful guide for government and funding agencies.
Keywords: ex-vivo; generation; metal wave-guides; near-field; performance; photoconductive emitters; Physics; quantum-cascade lasers; radiation; semiconductors; Terahertz; thz; time-domain spectroscopy

Global Picosecond Structural Dynamics of Orange Carotenoid Protein in Photo/Chemical Activated Signaling States - Deng, Y.; Xu, M.; Liu, H.; Blankenship, R.; Markelz, A. (APS 2017 S4.002, 2017)

Orange Carotenoid Protein Picosecond Dynamics Changes with Photo and Chemical Activation - Deng, Y. T.; Xu, M. Y.; Liu, H. J.; Blankenship, R. E.; Markelz, A. G. (Biophysical Journal, 2017)
Keywords: Biophysics

Hydration and temperature interdependence of protein picosecond dynamics - Lipps, F.; Levy, S.; Markelz, A. G. (Physical Chemistry Chemical Physics, 2012)
We investigate the nature of the solvent motions giving rise to the rapid temperature dependence of protein picoseconds motions at 220 K, often referred to as the protein dynamical transition. The interdependence of picoseconds dynamics on hydration and temperature is examined using terahertz time domain spectroscopy to measure the complex permittivity in the 0.2-2.0 THz range for myoglobin. Both the real and imaginary parts of the permittivity over the frequency range measured have a strong temperature dependence at >0.27 h (g water per g protein), however the permittivity change is strongest for frequencies <1 THz. The temperature dependence of the real part of the permittivity is not consistent with the relaxational response of the bound water, and may reflect the low frequency protein structural vibrations slaved to the solvent excitations. The hydration necessary to observe the dynamical transition is found to be frequency dependent, with a critical hydration of 0.19 h for frequencies >1 THz, and 0.27 h for frequencies <1 THz. The data are consistent with the dynamical transition solvent fluctuations requiring only clusters of similar to 5 water molecules, whereas the enhancement of lowest frequency motions requires a fully spanning water network.
Keywords: Chemistry; dielectric-relaxation; fluctuations; inelastic neutron-scattering; lysozyme; myoglobin; percolation; Physics; spectra; spectroscopy; terahertz beams; transition; water

Terahertz Response and Colossal Kerr Rotation from the Surface States of the Topological Insulator Bi2Se3 - Aguilar, R. V.; Stier, A. V.; Liu, W.; Bilbro, L. S.; George, D. K.; Bansal, N.; Wu, L.; Cerne, J.; Markelz, A. G.; Oh, S.; Armitage, N. P. (Physical Review Letters, 2012)
We report the THz response of thin films of the topological insulator Bi2Se3. At low frequencies, transport is essentially thickness independent showing the dominant contribution of the surface electrons. Despite their extended exposure to ambient conditions, these surfaces exhibit robust properties including narrow, almost thickness-independent Drude peaks, and an unprecedentedly large polarization rotation of linearly polarized light reflected in an applied magnetic field. This Kerr rotation can be as large as 65 degrees and can be explained by a cyclotron resonance effect of the surface states.
Keywords: bi2te3; Physics

The role of the protein surface on the local biological water dynamics - Liang, W.; He, Y. F.; George, D.; Markelz, A. G. (Biosensing Ii, 2009)
Protein function is reliant on structural flexibility and this flexibility is slaved to the surrounding solvent. Here we discuss how the exposed surface of the protein influences the solvent dynamics and thereby influences the protein's own structural dynamics. We discuss measurements of the THz absorption of water in the presence of hydrophilic and hydrophobic surfaces.
Keywords: alanine; dynamics; hydration; lysine; lysozyme; proteins; relaxation; spectroscopy; Terahertz; thz

Ultrafast Carriers Dynamics in GaSb/Mn Random Alloys - Ye, S.; Knab, J.; Chen, J.-Y.; Wang, S.; Cheon, M.; Luo, H.; Markelz, A. G. (Proceedings of the 28th International Conference on the Physics of Semiconductors, 2006)

Terahertz grid frequency doublers - Chiao, Jung-Chih; Markelz, Andrea; Li, Yongjun; Hacker, Jonathan; Crowe, Thomas; Allen, James; Rutledge, David (Proc. Sixth Intl. Symp. Space Terahertz Tech, 1995)

PROBING TERAHERTZ DYNAMICS IN SEMICONDUCTOR NANOSTRUCTURES WITH UCSB FREE-ELECTRON LASERS - Allen, S. J.; Craig, K.; Felix, C. L.; Guimaraes, P.; Heyman, J. N.; Kaminski, J. P.; Keay, B. J.; Markelz, A. G.; Ramian, G.; Scott, J. S.; Sherwin, M. S.; Campman, K. L.; et al. (Journal of Luminescence, 1994)
The UCSB free-electron lasers provide kilowatts of continuously tunable radiation from 120 GHz to 4.8 THz. They have the most impact on terahertz science and technology that require a tunable, high power source to explore non-linear dynamics or that sacrifice incident power to recover the linear response of systems with very small cross-section. We describe three experiments that demonstrate the utility of these lasers in experiments on the terahertz dynamics of semiconductor nanostructures: (i) terahertz dynamics of resonant tunneling diodes, (ii) saturation spectroscopy of quantum wells and (iii) photon-assisted tunneling in superlattices.

SPECIFIC-HEAT MEASUREMENTS ON SUPERCONDUCTING BI-CA-SR-CU AND TL-CA-BA-CU OXIDES - ABSENCE OF A LINEAR TERM IN THE SPECIFIC-HEAT OF BI-CA-SR-CU OXIDES - Fisher, R. A.; Kim, S.; Lacy, S. E.; Phillips, N. E.; Morris, D. E.; Markelz, A. G.; Wei, J. Y. T.; Ginley, D. S. (Physical Review B, 1988)